Reheating in holographic cosmology and connecting to Λ-MSSM constructions for particle physics - Nastase, Horatiu [UNESP] (Springer Nature, 2021)
In this paper we model the transition from the non-geometric holographic cosmology regime, to the usual radiation dominated (RD) cosmology, known as reheating in the case of (perturbative) inflation. We find that we can easily transition into any MSSM construction of intersecting D6-branes, via α′ corrections in the 3 dimensional field theory as well as in cosmology, followed by cosmological reheating via S-NS5-branes. Moreover, we can naturally obtain the (true) cosmological constant Λ of the observed order of magnitude. The resulting supersymmetry breaking is just outside the currently observed energies. The model is consistent with large (TeV scale) extra dimensions, but it prefers smaller ones, and the string scale is generically low.
Keywords: AdS-CFT Correspondence; Cosmology of Theories beyond the SM